Analysis of the Practicality of the E-PBL-STEM Learning Model Based on Tri N in Teaching Pressure Concepts - Widyawati, Ani; S, Suyanta; Kuswanto, Heru; Naf’an Amrurrahim, Ahmad (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the practicality level of the E-PBL-STEM learning model based on Tri N in teaching pressure concepts. This research is part of the Research and Development (R&D) process at the limited trial stage with a sample of one class. The instruments used for data collection include the lesson plan implementation sheet and a questionnaire assessing the practicality of the learning model by teachers. Data analysis techniques involve quantitative methods to calculate the percentage of observation scores on lesson plan implementation and teacher practicality questionnaires, followed by descriptive analysis. The research was conducted during the even semester of the 2022/2023 academic year. The results indicate that the E-PBL-STEM model based on Tri N is categorized as very practical, with a practicality percentage of 87.5% and a lesson plan implementation rate of 100%. The conclusion of this study is that each syntax of the E-PBL-STEM model based on Tri N is very practical to implement.